Perspektif Jean Piaget pada Proses Pewarisan Reog Obyog: Studi Kasus pada Masyarakat Transmigran Kota Banjarbaru Provinsi Kalimantan Selatan: Jean Piaget's Perspective on the Reog Obyog Inheritance Process: a Case Study in the Transmigrant Community of Banjarbaru City, South Kalimantan Province - Indriyani, Putri Dyah; Supriatna, Mamat (Anterior Jurnal, 2024)
This research aims to examine the process of inheritance in the Reog Obyog art in the Singo Budoyo community in Banjarbaru City, South Kalimantan. This inheritance process uses the theory put forward by Jean Piaget because it is considered appropriate to the conditions that occur in the field. This research uses a qualitative method with a case study approach. Data collection techniques use observation, interviews, and documentation. The data analysis carried out was by collecting data in the field then carrying out the coding and data reduction process and drawing conclusions. The results of the entire series of research that have been carried out have obtained answers to the research problem, namely the process of inheritance of the Reog Obyog art, there are four stages of development, namely sensorimotor, pre-personal, concrete operational, and formal operational which occur as a series of forms of cognitive development processes in children as inheritors of this art in society. transmigrants in Banjarbaru City. According to the results that have been found, this research concludes that in the dance context, children assimilate new movements by incorporating them into movement schemes that they already know. This is because the environment in which they live is not far from what they study.